Enhancement of power quality using U-SOGI based control algorithm for DSTATCOM - Atma Ram; Parsh Ram Sharma; Rajesh Kumar Ahuja (Ain Shams Engineering Journal, 2024)
The distributed static compensators (DSTATCOM) are connected at the distribution end to enhance the quality of power. The performance of DSTATCOM needs to be improved for better utilization and more ancillary services. In this regard, an upgraded second-order generalized integrator (U-SOGI) based adaptive control structure is developed for DSTATCOM. The proposed control algorithm is much simpler than transformation based techniques because this structure consists of two integrator, three mathematical operators and a damping factor. This control algorithm is utilized to extract the fundamental active and reactive components from the distorted load current. These components are further multiplied with respective voltage templates for generating the reference currents. Moreover, the damping factor is adjusted to mitigate the DC offset and damp out the oscillations presented in weight component during transient conditions. The proposed algorithm successfully performs the power quality tasks namely; a) harmonic mitigation, b) reactive current suppression, c) power factor correction, d) zero voltage regulation, and e) load balancing during various operating scenarios in distribution system. The robustness of proposed control is tested using MATLAB/Simulink results under both steady-state and dynamic conditions. Further, the superiority of the proposed technique is also presented by comparing it with classical techniques. From simulation study, it can be highlighted that the proposed controller successfully mitigates various power quality issues as per IEEE standards and performs way better than its counterparts under all possible operating conditions.